The General Surgical Care Practitioner Improves Surgical Outpatient Streamlining and the Delivery of Elective Surgical Care. Issue 6 (June 2013) - Kumar, Rohan; Debono, Lisa; Sharma, Paritosh; Basu, Sanjoy
The feasibility of implementing a surgical care practitioner (SCP) role for the delivery of secondary care within the general surgery department of a district general hospital was evaluated. Streamlining patients into an SCP-led 'one-stop' gallbladder clinic for symptomatic uncomplicated cholelithiasis led to a reduction in follow-up clinic workload for major elective laparoscopic work and more appropriate triaging of primary care referrals. Each of these improvements contributed to an efficient service model.